2010
DOI: 10.1007/s12015-010-9116-7
|View full text |Cite
|
Sign up to set email alerts
|

Probing Stemness and Neural Commitment in Human Amniotic Fluid Cells

Abstract: Recently, human amniotic fluid (AF) cells have attracted a great deal of attention as an alternative cell source for transplantation and tissue engineering. AF contains a variety of cell types derived from fetal tissues, of which a small percentage is believed to represent stem cell sub-population(s). In contrast to human embryonic stem (ES) cells, AF cells are not subject to extensive legal or ethical considerations; nor are they limited by lineage commitment characteristic of adult stem cells. However, to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 64 publications
1
35
0
Order By: Relevance
“…27,29,30 AFSC are being explored for use in tissue engineering applications for a variety of tissue types. This review focuses on cardiovascular cell types and tissue engineering, which are addressed further below, but AFSC are also being investigated for osteogenic, 13,31,32 renal, 33,34 myogenic, 35 epithelial, 36,37 and neuronal 14,[38][39][40][41][42][43][44][45] differentiation and tissue engineering. An area of contention that remains with AFSC is whether sorting for c-kit expression is necessary or appropriate.…”
Section: Identification Isolation and Culture Of Undifferentiated Smentioning
confidence: 99%
See 1 more Smart Citation
“…27,29,30 AFSC are being explored for use in tissue engineering applications for a variety of tissue types. This review focuses on cardiovascular cell types and tissue engineering, which are addressed further below, but AFSC are also being investigated for osteogenic, 13,31,32 renal, 33,34 myogenic, 35 epithelial, 36,37 and neuronal 14,[38][39][40][41][42][43][44][45] differentiation and tissue engineering. An area of contention that remains with AFSC is whether sorting for c-kit expression is necessary or appropriate.…”
Section: Identification Isolation and Culture Of Undifferentiated Smentioning
confidence: 99%
“…18 Oct4, Sox2, and Nanog, transcription factors necessary for maintaining pluirpotency in ESCs, also displayed mixed results across different studies of AFSC. 16,17,20,23,24,[29][30][31]35,37,[39][40][41]46,[48][49][50][51][52]54 In Vitro Cardiac Myocyte Differentiation of AFSC AFSC have been investigated for cardiac tissue engineering. 55 AFSC applications to in vitro cardiac tissue engineering are summarized in this section and Table 3.…”
mentioning
confidence: 99%
“…Many studies have demonstrated that the RBPJ-mediated NOTCH signaling pathway is indispensable for cells at various stages of development. Hence, we developed a protocol to better characterize the molecular profile of RBPJ expression in human amniotic fluid (AF) cells, a source of fetal cells with stem cell characteristics [18,19], and embryonal carcinoma (EC) NT2 cells, which have many shared features with human embryonic stem (ES) cells [20,21]. Since NT2 cells are known as a well-established cellular model of neuronal and glial differentiation [22][23][24], we also used this model system to compare RBPJ expression in undifferentiated cells and terminally differentiated neurons and astrocytes.…”
Section: Introductionmentioning
confidence: 99%
“…So far, neurogenic differentiation of AFS cells has been demonstrated in mouse, pig, and human (Mareschi et al 2009;Phermthai et al 2010;Jezierski et al 2010;Zheng et al 2010). It has been suggested that the efficiency of neurogenic differentiation depends on extracellular growth factors (Orciani et al 2008(Orciani et al , 2011.…”
Section: Neurogenic Differentiation Of Afs Cellsmentioning
confidence: 99%